ANALISA KERUSAKAN BELT CONVEYOR DAN PROSES PENYAMBUNGAN BELT CONVEYOR 23BC-04 LIMESTONE RAW MILL DI PT. SEMEN BATURAJA (PERSERO) TBK. - Nurrahmat, Fath; Safaruddin, Safaruddin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
PT. Semen Baturaja (Persero) Tbk is a State-Owned Enterprise of the Republic of Indonesia which was established on November 14, 1974 which is engaged in the cement industry sector. In the process of making cement, it cannot be separated from the means of material transportation to facilitate the process of moving materials at each stage of existing production. At PT. Semen Baturaja (Persero) Tbk, the means of transportation used for materials, one of which is a conveyor belt. Maintenance on the Belt Conveyor needs to be done so as not to tear or break the belt, and if it occurs, to deal with the problem, the Belt Conveyor is connected, namely by the method of Splicing and Mechanical Joint. The splicing method is splicing by gluing on both sides of the belt to be spliced, there are two methods in splicing, namely cold splicing and hot splicing, while the mechanical joint method is splicing by uniting the two sides of the belt with steel belt fasteners.